Adherence to the Dietary Approaches to Stop Hypertension Diet and Hyperuricemia: A Cross‐Sectional Study - Gao, Yun; Cui, Liu‐fu; Sun, Yuan‐yuan; Yang, Wen‐hao; Wang, Jie‐rui; Wu, Shou‐ling; Gao, Xiang (Arthritis care & research (2010), 2021)
Objective Although several individual nutrients/foods are associated with uric acid status, the association of overall diet quality with hyperuricemia remains unclear. The current study was undertaken to examine the association between adherence to the Dietary Approaches to Stop Hypertension (DASH) diet and the odds of having hyperuricemia in a Chinese adult population. Methods Included were 71,893 Chinese participants in the Kailuan I study and the Kailuan II study (mean age 51.4 years) who were free of gout prior to or in 2014. Dietary intakes were assessed using a validated food frequency questionnaire, and the DASH diet score was calculated based on consumptions of vegetables, fruit, dairy, beans, whole grains, meat, fat, sodium, and sugar‐sweetened beverages. Fasting blood samples were collected in 2014, and hyperuricemia was defined as serum uric acid concentrations of ≥7 mg/dl for men, and of ≥6 mg/dl for women. The association between DASH diet score and hyperuricemia was assessed using multiple logistic regression models, adjusting for age, sex, total energy, obesity, physical activity, education, smoking, alcohol drinking, blood pressure, fasting glucose, lipid profiles, renal function, and presence of cardiovascular disease. Results A High DASH diet score was associated with low odds of having hyperuricemia (adjusted odds ratio for quartile 4 versus quartile 1 0.70 [95% confidence interval 0.66, 0.75], P for trend < 0.001) after adjusting for potential confounders. The association between the DASH diet and hyperuricemia was more pronounced among older individuals (age ≥50 years), women, and physically inactive participants compared with their counterparts (P for interaction < 0.01 for all). Conclusion The DASH diet was associated with a low likelihood of having hyperuricemia in Chinese adults.